Synthesis, Characterization, Antimicrobial and Cytotoxic Studies on Some Novel Transition Metal Complexes of Schiff Base Ligand Derived From Sulfadiazine with Molecular Orbital Calculations - Elsayed, Badr A; Elhenawy, A.A; A. S. A, Sultanah (International Journal of Chemistry and Materials Research, 2014)
Some selected solid complexes of the Schiff base ligand HL derived from Sulfadiazine with Co(II), Ni(II) and Cu(II) ions were synthesized and characterized by Micro-analysis, FTIR, Electronic, Mass, and ESR Spectral Analyses, Magnetic susceptibility and Molar Conductance Measurements. The disappearance of ν(O-H) hydroxyl band of the phenolic and the lowering shift of the stretching frequency of the ν(CH=N) azomethine band in the ligand after complexation, indicated the coordination through the phenolic oxygen atom (after deprotonation) and azomethine nitrogen atom respectively of the Schiff base ligand HL. The lower values of molar conductance indicate the non-electrolytic nature of these complexes. The ESR spectrum of the HL copper complex has octahedral geometry. The molecular structures of the investigated compounds were studied by PM3 method, also the heat of formations, HOMO, LUMO and dipole moments were calculated to confirm the geometry of the ligand and the it's complexes. The antimicrobial screening of the synthesized compounds HL and its complexes 1-3 were investigated. The Schiff base ligand HL showed weaker to significant activity against one or more bacterial and fungal strains. In most of the cases higher activities were exhibited upon coordination with metal ions(II). In addition, calculations in silico, the Pharmacokinetic parameters have promising features for applying the ligand as drug.